School-Based Enterprises: Rural Education Through Action Learning - Paul F. DeLargy (Educational Considerations, 1986)
School based enterprises offer an attractive solution to seemingly different problems - improving rural schools and supporting rural economic growth. As such, they demonstrate the very best in rural creativity.